Sie sind auf Seite 1von 6

P (A B)

 1 − P (A C ∩ B C ) 1 − P (A C ∪ B C ) 1 − P (A C )P(B C ) P (A C ∩ B C )

P(A B) = 1 P (A B) C = 1 P(A C B C )

P ( n

i=1 E i )

n

n

i=1 P (E i )

max i P (E i )

i=1 P (E i )

min i P (E i )

max i P (E i )

min i P (E i )

A : B :

P (A B) = 0.17 P (A) = 0.12 P (A B) = 0.06

P(A B) = P(A) + P(B) P(A B)

P (B) = P (A B) + P (A B) P (A) = 0.17 + 0.06 0.12 = 0.11

X

f (x) = 1 0 x 1

f (x)

F(x) = x f(t) dt = x 1 dt = [t] x = x 0 = x

0

0

0

x 75 F (x 75 ) = 0.75 F (x 75 ) = x 75 x 75 = 0.75

1 < x <

x 1 1 1

1

x 3

1

x

x

1

1

x

1

3

1 2 1 < x <

x

F(x) = x

1

t

1

2 dt = 1

t

x

1

=

1

t

1

x

= 1

1

1

x = 1 1

x

p e x (1 + e x ) 2

 log ((1 − p) /p) p/ (1 − p) (1 − p) /p 1/ (1 + e x )

log (p/ (1 p))

x
e −t
F(x) =
e −t ) 2 dt
(1 +
−∞
u(t) = 1 + e −t du = −e −t dt
u(x)
1+e −x
1+e −x
1 e x e −x
−1
−1
1
e x
F(x) =
du =
du =
= =
u 2
u 2
u
∞ 1 + e −x
e −x (e x + 1) =
e x + 1
u(−∞)
x p F (x p ) = p
F(x p ) =
p
e x p
p
e x p + 1 =
e x p =
p (e x p
+ 1)
e x p =
pe x p + p
e x p − pe x p =
p
e x p (1 − p) =
p
p
e x p =
1 − p

x p = log

1 p

p

cx k c > 1 0 < x < 1 c

k + 2

1

k

2

1

k+1

k 1 k k + 1

 1 0 cx k dx = c x k+1 + 1 1 k + c 1 x k+1 1 k + c 1 (1 − 0) = c k = 0 = k + 1 0

c

k + 1 = 1 c = k + 1

1

f (x) = 1 2 e x/2 x > 0

F (x)
0
1 2 e −t/2 dt = −e −t/2 x = e −t/2
= e 0 − e −x/2 = 1 − e −x/2
F(x) = x
0
x
0
x 50 F (x 50 ) = 0.5
F(x 50 ) = 0.5
1 − e −x 50 /2
= 0.5
e −x 50 /2
= 0.5
x
50 /2 = − log 1 2
x
50 /2 = log (2)
x 50 = 2 log (2) ≈ 1.386

x 50 /2 = log

1

2

2xe x 2 x > 0

F (x)

F(x) = x 2te t 2 dt

0

u(t) = t 2 du = 2tdt

F(x) =

u(x)

u(0)

e u du = x 2 e u du = [e u ] x 0 2 = e 0

0

x 50 F (x 50 ) = 0.5

F(x 50 ) = 0.5

1 e x 50 2 = 0.5

= 0.5

e x

2

50

 2 log −x 50 =

e x 2 = 1 e x 2

1 2

 2 log (2) x 50 =

x 50 = log (2) 0.833

h(x) 0 < h(x) < x = 1, 2, c

1

I

1 + x=1 h(x)

x=1 h(x)

x=1 h(x) 1

h(I)

I

I

, I c · h(x)

0 < c · h(x) < ∞ x c·h(x) = 1
I
c · h(x)
= 1
x=1
c
I
h(x) = 1
x=1
c = x=1 h(x) −1
I